The Indonesian Version of the Skills, Confidence, and Preparedness Index (SCPI) was tested for reliability and validity in type 2 diabetes patients - Kurnia, Anih; Said, Farida Mohd; Paduragan, Santhna Letchmi (International Journal of Health Sciences, 2024)
Although several diabetes self-care management tools have been created, very few provide preparation for diabetes self-care behavior management. Three essential components of diabetes self-care management are measured by the assessment tool "Skills, Confidence & Preparedness Index (LMC) (SCPI)": Knowledge of skills, Confidence in one's ability to use skills, and Readiness to put skills into practice. This study aims to validate, translate, and adapt the SCPI for usage with Indonesian adults with type 2 diabetes. Methods: The American Academy of Orthopedic Surgeons Evidence Based Medicine Committee (AAOS) criteria for modifying the scale were adhered to in this study. Evaluate average variance, Cronbach alpha, and composite reliability to test validity and reliability. Specifically, determinant coefficient testing and model appropriateness testing are used to assess goodness of fit. Examine the valid R-squared statistical value for every relationship to determine the test. If the p-value is less than 0.05, then there is a direct and indirect association to be seen if the variable is significant Result: Cronbach's alpha > 0.60 indicates strong internal consistency for the Indonesian SCPI version or I-SCPI. For every variable, the AVE value is larger than 0.50, while the CR value exceeds 0.70. This indicates that all legitimate indicators converge to form the variables for which they are intended. The R-Square values of 0.312 and 0.536 for the variables of preparedness and confidence are used to calculate the degree of good fit. This number indicates that the Preparedness variable is only partially explained by the Confidence and Preparedness variables (5.36%), with other variables accounting for the remaining 94.64%. Furthermore, the Skill/Knowledge, Confidence, and Preparedness factors account for only 3% of the variance in the Confidence variable, with the remaining 97% explained by variables outside the model. Conclusion: We developed an Indonesian version of SCPI through cross-cultural translation and adaption. The I-SCPI is reliable and valid for assessing the level of self-management in type 2 diabetes patients in Indonesia